(untitled) (Bangladesh Journal of Medical Biochemistry, 2024)
Adiponectin is a hormone, secreted from adipose tissue. It is inversely correlated with body fat mass. This hormone has also anti-inflammatory and ant-iatherogenic properties. This study was purposed to explore the relationship between serum adiponectin concentration and lipid profile. This cross-sectional analytical study was carried out in the Department of Biochemistry, Bangabandhu Sheikh Mujib Medical University (BSMMU) from March 2016 to February 2017. By non-probability sampling, a total of 156 study subjects were selected from apparently healthy adult individuals attending outpatient department of BSMMU. Serum adiponectin level positively correlated with serum HDL cholesterol (r=0.246, p value 0.002) concentrations and negatively correlated with serum total cholesterol (r=-0.171, p value 0.033) and serum triacylglycerol level (r=-0.3, p value 0.00). So, from this study it can be concluded that adiponectin has an important role in the metabolism of lipid profile components and responsible for controlling the concentration of serum lipid profile components. When adiponectin concentration of blood increases it is responsible for raised serum HDL-C concentration and decreased total cholesterol and triacylglycerol concentration. Bangladesh J Med Biochem 2019; 12(1): 6-10